effects of ration level on feed intake and growth, and compensatory growth after restricted feeding, in turbot Scophthalmus maximus L - Saether, B.S; Jobling, M (Aquaculture research, 1999)
Feed intake and growth were studied in groups of turbot fed daily rations of 0.25%, 0.38% and 1% of body weight day(-1) for 41 days. Then, all groups were fed 1% of body weight day(-1) for the next 34 days. The two restricted rations resulted in reduced growth rates (30% and 60% of fully fed controls), and there was a tendency for increased growth heterogeneity (coefficient of variation increased from about 100% to about 150%) compared with controls on full rations. Nevertheless, restricted rations did not result in any increase in size heterogeneity with the passage of time: the coefficient of variation for weight changed little irrespective of feeding treatment. The turbot became hyperphagic and displayed compensatory growth after the change from restricted to excess feeding, with compensatory growth being most marked among the fish that had been subject to the most severe feed restriction. The results provided some evidence of increased variability in feeding and growth within groups of turbot fed restricted rations, possibly as a result of the establishment of weak feeding hierarchies. When feeding restrictions were lifted, the turbot that had reduced growth under feed restriction were able to completely compensate for lost growth.